Biased Yes/No Questions : The Role of VERUM - Romero, Maribel (My University, 2006)
Some information-seeking yes/no (yn)-questions convey an epistemic bias of the speaker. Examples are questions with the particle really (e.g., Did he really bring a present?), negative questions with preposed negation (e.g., Doesn’t John drink?), and in some contexts even regular questions (e.g., Is it raining?). The goal of this paper is to compare two main approaches to biased yn-questions – the VERUM approach and the Decision Theory approach – and to argue that, while certain formal notions from Decision Theory are important, the operator VERUM is needed to derive the full range of data. Furthermore, the paper explores the behavior of VERUM and really as expressive items.
Keywords: 400